2012
DOI: 10.1016/j.appet.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of label information on dark chocolate acceptability

Abstract: a b s t r a c t 25The aim of the present work was to study how the information on product labels influences consumer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 25 publications
2
43
1
2
Order By: Relevance
“…taste, smell, texture) and extrinsic product properties such as package elements or labels (Torres-Moreno, Tarrega, Torrescasana, & Blanch, 2012). In various laboratory (Garcia-Bailo, Toguri, Eny, & El-Sohemy, 2009;Hasselbalch, Heitmann, Kyvik, & Sorensen, 2008) and real life studies (De Graaf et al, 2005), liking ratings have been shown to relate to food choice and food intake.…”
Section: Introductionmentioning
confidence: 99%
“…taste, smell, texture) and extrinsic product properties such as package elements or labels (Torres-Moreno, Tarrega, Torrescasana, & Blanch, 2012). In various laboratory (Garcia-Bailo, Toguri, Eny, & El-Sohemy, 2009;Hasselbalch, Heitmann, Kyvik, & Sorensen, 2008) and real life studies (De Graaf et al, 2005), liking ratings have been shown to relate to food choice and food intake.…”
Section: Introductionmentioning
confidence: 99%
“…In an early double-blind trial with branded analgesics, participants perceived the branded pain killer to be more effective than a chemically identical unbranded analgesic [3]. Brands are very powerful and have a high impact on people’s economic decisions, to the degree that consumers oftentimes prefer products of brands even among almost identical products [4]. Within the present study we set out to explore how brands are processed in the brain and how fictitious brand information can alter the perception and the neural correlates of product exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Despite such study limitations, other research links chocolate consumption to feelings of guilt (Macht and Dettmer, 2006;M€ uller et al, 2008). Recent data demonstrate that on-pack claims on a product containing a high percentage of cocoa did not generate higher expectations than regular cocoa-containing dark chocolate (Torres-Moreno et al, 2012). Interestingly, it is possible that the actual content of cocoa in products is not indicative of the health benefits of dark chocolate.…”
Section: The Cocoa Flavanol Consumer?mentioning
confidence: 99%